The Role of Culture on Female Labor Supply: Evidence from Turkey - Pelin Akyol; Cagla Okten (Institute of Labor Economics (IZA), 2019)
This paper investigates the effect of culture on female labor market outcomes using new micro-level data on two distinct Muslim denominations in Turkey: Sunni and Alevi Muslims. We find a positive and significant effect of being an Alevi Muslim on female labor force participation and employment probability compared to a Sunni Muslim whereas there are no significant differences in male labor market outcomes between the two denominations. We provide evidence that Alevi Muslims have more gender equal views regarding the role of women in the labor market and argue that differences in gender views drive the results.
Keywords: J16; J21; 330; female labor force participation; culture; gender